An Analysis of Cybersecurity Policies and Practices in Public Administration - Aulia Ramdhani Arief (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The purpose of this research was to assess the strengths and weaknesses of a public administration organization's hacking policies and practices. According to the findings, the company has a solid cybersecurity base thanks to its comprehensive policies and ongoing training and awareness programs. Nonetheless, there were also opportunities for development, such as in access controls and vulnerability evaluations. A more thorough cybersecurity policy, the use of role-based access control, and more frequent and thorough vulnerability assessments and penetration testing were among the best practices and improvement suggestions uncovered by the research. The company will be better able to safeguard sensitive data and prevent future attacks by implementing these suggestions. This research serves as a useful reminder of the significance of cybersecurity in public administration and emphasizes the need for constant vigilance and advancement in order to remain one step ahead of new threats.